2013
DOI: 10.2174/13816128113199990337
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy of Candidate Universal Influenza A Nanovaccines Produced in Plants by Tobacco Mosaic Virus-based Vectors

Abstract: A new approach for super-expression of the influenza virus epitope M2e in plants has been developed on the basis of a recombinant Tobacco mosaic virus (TMV, strain U1) genome designed for Agrobacterium-mediated delivery into the plant cell nucleus. The TMV coat protein (CP) served as a carrier and three versions of the M2e sequence were inserted into the surface loop between amino acid residues 155 and 156. Cysteine residues in the heterologous peptide were thought likely to impede efficient assembly of chimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 63 publications
1
58
0
Order By: Relevance
“…In this study, a plant-based expression system was chosen as such systems have been shown to have promise for vaccine development, for example Hepatitis B virus vaccine which is the first plant-based vaccine produced by tobacco in 1992 (Mason et al 1992), Influenza virus vaccine (Petukhova et al 2013), and Ebola virus vaccine (Qiu et al 2014), both produced in N. benthamiana. Plant systems are favoured as they are considered safe, low-cost, rapid to upscale and less vulnerable to contamination with human or animal pathogens compared with traditional inactivated vaccines and animal or microbial cell culture-based vaccines (reviewed in Rybicki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a plant-based expression system was chosen as such systems have been shown to have promise for vaccine development, for example Hepatitis B virus vaccine which is the first plant-based vaccine produced by tobacco in 1992 (Mason et al 1992), Influenza virus vaccine (Petukhova et al 2013), and Ebola virus vaccine (Qiu et al 2014), both produced in N. benthamiana. Plant systems are favoured as they are considered safe, low-cost, rapid to upscale and less vulnerable to contamination with human or animal pathogens compared with traditional inactivated vaccines and animal or microbial cell culture-based vaccines (reviewed in Rybicki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of high-yield expression of H5 haemagglutinin-derived VLPs via transient expression [44] 10 million vaccine dose "rapid fire" milestone by Medicago Inc. in DARPA Blue Angel programme [50] Human clinical trial of plant-made H5N1 vaccine candidate [47] HA-only VLPs produced for H7N9 outbreak virus [54] Phase 1 trials of H1N1pdm and HPAI H5N1 HA-derived plant-made products [48] Testing of plant-made engineered soluble trimeric HA (H1N1pdm) in mice [58] Adjuvanting of monomeric H1N1pdm HA with SiO 2 and bis-(3′,5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) [59] Emergency response influenza vaccine candidates made in South Africa [43] Conjugation of plant-made HA to TMV particles and successful testing in mice [60] Elicitation of neutralising Ab with elastin-like polypeptide fused with stabilised soluble trimer-forming H5N1 HA [61] Presentation of M2e epitope on surface of rTMV virions elicits protective immunity to homologous and heterologous challenge in mice [64] Papillomaviruses Proof of efficacy of a plant-made Cottontail rabbit and Rabbit oral papillomavirus vaccines [74,75] High yields of HPV-16 L1 and VLPs via agroinfiltration-mediated transient expression or via transplastomic expression [76,77] Transplastomic expression of capsomere-forming HPV-16 L1 fused with Escherichia coli LTB as a built-in adjuvant [78] Successful expression of HPV-8 and Bovine papillomavirus L1 VLPs in plants [79,80] Co-expression of HPV-16 L1 with E coli LTB and oral immunisation elicits increased intestinal mucosal IgA responses to L1 [90] High-yield plant transient expression of chimaeric L1::L2 VLPs and proof of increased breadth of immune response [91] rPVX CP fusion with L2 108-120 epitope yields well and elicits high-titre anti-L2 protein sera in mice [97] Plant production, scale-up and protective efficacy in mouse model of therapeutic E7GGG-LicKM fusion protein vaccine [85][86][87] Plant expressed HPV-16 L1 with C-terminal string of E6 and E7 T-cell epitopes is viable prophylactic/therapeutic vaccine candidate [98] Production and proof of efficacy in mice of soluble E7GGG therapeutic vaccine in transplastomic Chlamydomonas reinhardtii [100] Proof of yield increase and eff...…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Antibodies to М2e, induced by natural infection or vaccination, appear in small quantities; and yet there are many ways that its immunogenicity can be increased [6][7][8][9][10][11][12][13][14][15][16][17][18], such as fusing it to an appropriate protein carrier [8,[13][14][15][16][17][18]26].…”
Section: Introductionmentioning
confidence: 99%